Kimura Disease of the Epiglottis - Badr, AbdullGaffar (Humana Press Inc, 2008)
Kimura disease is a distinct clinicopathological entity of a benign chronic inflammatory disorder of unknown etiology. It is endemic in Oriental Asians, but sporadic and relatively rare in the West, both in whites and blacks alike. It usually presents as a mass lesion, most commonly in the head and neck region. It had for a long time been confused as synonymous with angiolymphoid hyperplasia with esinophilia. It can impose a challenging diagnosis both clinically and pathologically, especially in non-endemic areas with unusual sites involvement. Even though it is a benign lesion, it can be life-threatening in the epiglottis with a risk of airways obstruction. So far, one case had been reported in the epiglottis with upper respiratory tract obstruction. We report a similar case with a brief review of the literature.